The interpretation of image-map as a proposal for teaching-learning of geography in high school - Soares, Marcelo Henrique Viana; Soares, Lucas Pereira; Cunha, Fábio Souza e Silva da; Lima, Ernane Cortez (Geosaberes; Vol 9 No 17 (2018): Jan - Apr, 2017)
Faced with the popularization of geotechnologies, it becomes necessary pedagogical actions that explore their potentials in basic education, given that these tools provide support to the teaching-learning process. In this perspective, this article approaches the image-map as didactic material worked in the discipline of Geography in a school in the city of Sobral - CE. For this purpose, the Landsat 8 satellite image was used, which was manipulated in the Geographic Information System (GIS) manager QGIS 2.8. Thus, it prepared a low-cost product, updated and adapted to the school context. As conclusions, it is noticed that the students have more contact with the geotechnologies outside the classroom, thus revealing the little use of these materials in the school. It was also verified that the content approach helps them in understanding about such resources and that the interpretation of the picture card has contributed to the learning of their geographical space.
Keywords: Cartografia Escolar; Ensino de Geografia; Geotecnologias